PENGARUH KARAKTERISTIK WIRAUSAHA TERHADAP KEBERLANGSUNGAN USAHA DI PONDOK PESANTREN KIAI MAROGAN KECAMATAN SUKARAME PALEMBANG - Giani, Malita; Jawasi, Jawasi (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
This research is entitled the influence of entrepreneurial characteristics on business sustainability at the Kiai Marogan Islamic boarding school, Sukarame District, Palembang. The aim of this research is to determine the influence of entrepreneurial characteristics on business sustainability at the Kiai Marogan Islamic Boarding School, Sukarame District, Palembang. The type of research used is quantitative using a causal associative approach, while the data collection techniques in this research are observation, interviews, questionnaires and documentation. In this study, the population and sample were boarding school administrators, totaling 30 people. Data testing was carried out using SPSS version 26 software tools. The analysis method used was simple linear regression analysis. The partial results of this research (t test) show that the entrepreneurial characteristics variable has a positive and significant effect on the business sustainability variable at the Kiai Marogan Islamic Boarding School, Sukarame District, Palembang. This is proven by tcount > ttable, namely 8.628 > 1.701 and the significance value is smaller than 0.05, namely 0.001 < 0.05. Then the Adjusted R2 value is 0.727 or equal to 72.7%. This figure means that 72.7% of the entrepreneurial characteristics variable (X) influences the business sustainability variable (Y). Meanwhile, the remaining 27.3% is influenced by other variables outside this regression equation or variables that were not studied.